A Solution‐Processable Polymer Photocatalyst for Hydrogen Evolution from Water. Issue 22 (1st September 2017) - Woods, Duncan J.; Sprick, Reiner Sebastian; Smith, Charlotte L.; Cowan, Alexander J.; Cooper, Andrew I.
Abstract: Direct photocatalytic water splitting is an attractive strategy for clean energy production, but multicomponent nanostructured systems that mimic natural photosynthesis can be difficult to fabricate because of the insolubility of most photocatalysts. Here, a solution‐processable organic polymer is reported that is a good photocatalyst for hydrogen evolution from water, either as a powder or as a thin film, suggesting future applications for soluble conjugated organic polymers in multicomponent photocatalysts for overall water splitting. Abstract : Multicomponent nanostructured systems that mimic natural photosynthesis can be difficult to fabricate because of the insolubility of most photocatalysts. Here, a solution‐processable organic polymer is reported that is a good photocatalyst for hydrogen evolution from water, either as a powder or as a thin film, suggesting future applications for soluble conjugated organic polymers in multicomponent photocatalysts for overall water splitting.